PERAN ELECTRONIC WORD OF MOUTH DAN TRUST TERHADAP MINAT BERKUNJUNG WISATAWAN DI MASA PANDEMI (Pada Objek Wisata Air Terjun Tegenungan) - Muhamad Iqbal Aziz; Anak Agung Elik Astari; Ni Luh Indiani (Nusantara Hasana Journal, 2022)
This study took the object of Tegenungan Waterfall with the variables Electronic Word Of Mouth, trust and Tourist Visiting Interests in Mada Pandemic, the purpose of this study was to determine the role of Electronic Word Of Mouth and Trust on Tourist Visiting Interests in the Pandemic Period. Quantitative research methodology with questionnaires, population and sample of 120 respondents. Then analyzed the data obtained by using multiple regression analysis. This analysis includes: validity and reliability, classical assumption test, multiple regression analysis, hypothesis testing through t and F tests, and analysis of the coefficient of determination (R2). Where the variables of Visiting Interest (Y), Electronic Word Of Mouth (X1), Trust (X2) were tested using the t-test indicating that the two independent variables significantly influenced visiting interest, as the dependent variable with a significant value generated of 0.00 from each - each Independent variable. Then through the F test, it shows that the Electronic Word Of Mouth and Trust variables have a significant effect on the visiting interest variable with a significant value of 0.00. The R-square figure of 45.5% indicates that the percent of the variable interest in visiting can be explained through the three independent variables in the regression equation, while the remaining 54.5% comes from or is based on other variables outside the three variables used in this study.